2015
DOI: 10.1097/wad.0000000000000076
|View full text |Cite
|
Sign up to set email alerts
|

Dantrolene, A Treatment for Alzheimer Disease?

Abstract: Alzheimer's disease (AD) is a fatal progressive disease and the most common form of dementia without effective treatments. Previous studies support that the disruption of endoplasmic reticulum (ER) Ca2+ via overactivation of Ryanodine receptors (RYRs) plays an important role in the pathogenesis of AD. Normalization of intracellular Ca2+ homeostasis could be an effective strategy for AD therapies. Dantrolene, an antagonist of RYRs and an FDA approved drug for clinical treatment of malignant hyperthermia and mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 108 publications
1
27
0
Order By: Relevance
“…Previous studies on the ADNI dataset have also reported significant genetic interactions for CACNA1C using Positron Emission Tomography (PET) imaging (Koran et al, 2014) and LASSO screening with candidate phenotypes (Yang et al, 2015), which all involve certain ‘ conditioning ’ for the contribution from CACNA1C to be detected. Animal AD models have confirmed several results from human studies (Hopp et al, 2014) and related pathways have been identified as a therapeutic target (Liang and Wei, 2015) for AD. Interestingly, a recent multi-site large-scale voxel level functional connectivity study, which included 939 subjects, has revealed that functional connectivity patterns in the orbitofrontal cortex region are significantly altered in depression patients (Cheng et al, 2016).…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies on the ADNI dataset have also reported significant genetic interactions for CACNA1C using Positron Emission Tomography (PET) imaging (Koran et al, 2014) and LASSO screening with candidate phenotypes (Yang et al, 2015), which all involve certain ‘ conditioning ’ for the contribution from CACNA1C to be detected. Animal AD models have confirmed several results from human studies (Hopp et al, 2014) and related pathways have been identified as a therapeutic target (Liang and Wei, 2015) for AD. Interestingly, a recent multi-site large-scale voxel level functional connectivity study, which included 939 subjects, has revealed that functional connectivity patterns in the orbitofrontal cortex region are significantly altered in depression patients (Cheng et al, 2016).…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, treatment of FAD transgenic mice with dantrolene has been found by several laboratories to be effective in reversing a range of AD features, including aberrant ER Ca 2+ signaling, disrupted hippocampal synaptic plasticity mechanisms, behavioral deficits, and Aβ plaque deposition [84]. In our laboratory, we found that a 4-week treatment with a brain penetrant nanocrystal formulation of dantrolene normalized the elevated hippocampal RyR2 expression and aberrantly high somatic and dendritic RyR Ca 2+ responses in pyramidal neurons from 3xTg and APP/PS1 FAD mice, restored normal short-term and long-term synaptic plasticity mechanisms in 3xTg mice, and reduced the levels of soluble and insoluble Aβ in cortex and hippocampus of APP/PS1 mice [22].…”
Section: Opportunities For Therapeuticsmentioning
confidence: 99%
“…6D) is structurally very similar to LPA; however, two of its hydroxyl groups are esterified with fatty acid chains, and the third hydroxyl group is esterified with phosphoric acid. It is both a modulator of membrane shape and a second messenger [see (Ammar et al, 2014) for review]. PA displays a variety of functions, being involved in the intracellular transport of target proteins via PA vesicles (Henkels et al, 2016) and playing a major role in the development of the nervous system (Ammar et al, 2014).…”
Section: Signal Transductionmentioning
confidence: 99%
“…It is both a modulator of membrane shape and a second messenger [see (Ammar et al, 2014) for review]. PA displays a variety of functions, being involved in the intracellular transport of target proteins via PA vesicles (Henkels et al, 2016) and playing a major role in the development of the nervous system (Ammar et al, 2014). Similarly, cyclic phosphatidic acid (cPA), a naturally occurring analog of LPA (Fig.…”
Section: Signal Transductionmentioning
confidence: 99%
See 1 more Smart Citation